VD_FINDINFO HC / 2009 / 271 vom 18. September 2009 - VD Tribunal cantonal (2009)
SUSPENSION DE LA PROCÉDURE, DÉCISION INCIDENTE, POUVOIR D'EXAMEN | 124a CPC, 451 ch. 7 CPC, 452 al. 1 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 456a al. 2 CPC, 465 al. 1 CPC, 471 al. 3 CPC